Determinants of Income Inequality in Yogyakarta Special Region Province Viewed from Jasser Auda Maqashid Syari'ah - darwis harahap (Institut Agama Islam Negeri Padngsidimpuan, 2023)
This study aims to analyze the determinants of income inequality in the province of the Special Region of Yogyakarta in terms of Jasser Auda's maqashid shari'ah. The study was carried out as a quantitative method using secondary data in the type of time series for the 2014-2020 period. The results of the E-views 10 study show positive results on the economic growth variable on income inequality in the DI Yogyakarta province. Then the variables that have no effect on income inequality are population and education. Maqashid syari'ah is a relevant approach as a basis for expanding economic development. The wholeness approach is believed to be better at monitoring the causes and effects of events such as the inequality that occurred in the province of DI Yogyakarta. The government is expected to adopt policies to improve economic stability in the DI Yogyakarta province. This study is expected to be a reference material and information for policy makers in making decisions. For further researchers, they can add related variables from this study in order to add novelty in follow-up studies.